Are port success driven by trade, location or services - Kor, Valerie Xiang Jun (2018)
The paper will look at past literature that studies port success. Spotlight is on services being a driver in ports’ success. The neglect in comparing these three factors in past literature leads to the current research gap. Port success relies on many factors and the main ones are trade, location and services of course there are few other factors that many industry players think that is important. Hence, to verify the main drivers for port success, interviews were done to seek their opinions, specifically on the three main factors. Trade was found to be the biggest driver, coming very close next is the location and lastly almost all agreed that services drive port success further by building on trade on location. The interviewees also unanimously pointed out political stability, governance is also another crucial driver to a port’s success. In addition to comparing the three factors, a case study will compare PSA and Port of Tanjung Palapas, specifically with regards to MAERSK’s exit from the former for Port of Tanjung Pelapas. Throughout me and my groupmates’ papers, we would safely say no one port can be successful with a standalone factor, rather a successful port is the one with a myriad of them.